Physical and chemical struggle measures against parasitic nematodes that cause diseases in crops in The Province of Surxondary (In the case of southern districts) (Texas Journal of Agriculture and Biological Sciences, 2023)
Various methods and tools are used to protect agricultural crops from nematodes. It is important to determine the composition of species of nematodes in the fight against them, to know their biology, ecology and many other specific features. The following methods are used in the fight against parasitic nematodes